2023
DOI: 10.1038/s41419-023-05695-2
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA DLX6-AS1 is the key mediator of glomerular podocyte injury and albuminuria in diabetic nephropathy by targeting the miR-346/GSK-3β signaling pathway

Abstract: Progressive albuminuria is the primary clinical symptom of diabetic nephropathy (DN), leading to a gradual decline in kidney function. DLX6-AS1 was the first reported long non-coding RNA (lncRNA) to participate in organogenesis and play crucial roles in the brain or neural cell development. Herein, we investigated the DLX6-AS1 (Dlx6-os1 in mice) role in DN pathogenesis. We found that DLX6-AS1 expression in DN patients correlated with the extent of albuminuria. Dlx6-os1 overexpression induced cellular damage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…Our results showed a low miR‐346 expression in DN patients and HG‐stimulated HRMCs. A recent paper reported that miR‐346 promoted cellular damage and inflammatory response of podocytes in DN through the lncRNA DLX6‐AS1/miR‐346/GSK‐3β pathway 18 . Our work showed the involvement of miR‐346 in Alisol A‐induced effects on HG‐stimulated HRMC injury.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our results showed a low miR‐346 expression in DN patients and HG‐stimulated HRMCs. A recent paper reported that miR‐346 promoted cellular damage and inflammatory response of podocytes in DN through the lncRNA DLX6‐AS1/miR‐346/GSK‐3β pathway 18 . Our work showed the involvement of miR‐346 in Alisol A‐induced effects on HG‐stimulated HRMC injury.…”
Section: Discussionsupporting
confidence: 62%
“…17 pathway. 18 Our work showed the involvement of miR-346 in Alisol A-induced effects on HG-stimulated HRMC injury.…”
Section: Discussionmentioning
confidence: 56%
“…It was needed to research how lncRNA SNHG1 regulating SERPINA3 mRNA. Combining with our result that lncRNA SNHG1 located mainly in the cytoplasm, we sought much evidence in literatures that lncRNAs locating in cytoplasm often depend on sponging miRNAs [41,42]. But it is limited of just focusing on this sponging mechanism, because more and more scientists have proven that lncRNAs also could interact with proteins to in uence target genes [3].…”
Section: Discussionmentioning
confidence: 87%
“…A plethora of research has highlighted the role of podocyte injury, characterized by a reduction in podocyte count/density and foot process fusion/effacement, in DN progression. This injury is viewed as a significant contributor to the development of albuminuria [28][29][30]. Nevertheless, the mechanisms through which basement membrane thickening leads to albuminuria are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%